2010
DOI: 10.1074/jbc.m109.025684
|View full text |Cite
|
Sign up to set email alerts
|

SPARC Suppresses Apoptosis of Idiopathic Pulmonary Fibrosis Fibroblasts through Constitutive Activation of β-Catenin

Abstract: Idiopathic pulmonary fibrosis (IPF) is a poorly understood progressive disease characterized by the accumulation of scar tissue in the lung interstitium. A hallmark of the disease is areas of injury to type II alveolar epithelial cells with attendant accumulation of fibroblasts in areas called fibroblastic foci. In an effort to better characterize the lung fibroblast phenotype in IPF patients, we isolated fibroblasts from patients with IPF and looked for activation of signaling proteins, which could help expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 43 publications
4
112
0
Order By: Relevance
“…Previous studies have shown that cycloheximide alone is insufficient to induce fibroblast apoptosis (11,35), a finding that was confirmed in a subset of experiments for each of the different fibroblast populations studied. Together, these findings are consistent with prior studies showing that normal fibroblasts are relatively resistant to Fas-mediated apoptosis, that IPF lung fibroblasts have increased resistance to Fas-mediated apoptosis compared with normal lung fibroblasts, and that cycloheximide "sensitizes" normal and IPF fibroblasts to undergo robust apoptosis upon Fas activation (8,10,12,(33)(34)(35)(37)(38)(39). Additionally, these findings demonstrate that IMR-90 and CCL-210 fibroblasts exhibit Fas-induced apoptotic responses that are indistinguishable from primary normal lung fibroblasts isolated from lung explants.…”
Section: Ipf Lung Fibroblasts Have Decreased Susceptibility To Fas-mesupporting
confidence: 90%
“…Previous studies have shown that cycloheximide alone is insufficient to induce fibroblast apoptosis (11,35), a finding that was confirmed in a subset of experiments for each of the different fibroblast populations studied. Together, these findings are consistent with prior studies showing that normal fibroblasts are relatively resistant to Fas-mediated apoptosis, that IPF lung fibroblasts have increased resistance to Fas-mediated apoptosis compared with normal lung fibroblasts, and that cycloheximide "sensitizes" normal and IPF fibroblasts to undergo robust apoptosis upon Fas activation (8,10,12,(33)(34)(35)(37)(38)(39). Additionally, these findings demonstrate that IMR-90 and CCL-210 fibroblasts exhibit Fas-induced apoptotic responses that are indistinguishable from primary normal lung fibroblasts isolated from lung explants.…”
Section: Ipf Lung Fibroblasts Have Decreased Susceptibility To Fas-mesupporting
confidence: 90%
“…This process, although unable to replace tissue or organ function (eg, myocardial scarring after infarction), is in most cases controlled, and its regulation is strictly dependent on the resolution of the underlying inflammatory spur. SPARC is a matricellular glycoprotein involved in fibrosis 3,4,7,34 through unknown mechanisms, in addition to its role in collagen and ECM deposition. 35,36 An impaired ECM deposition or the absence of SPARC is associated with increased inflammatory infiltration and immune cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC was originally identified as a stress response gene (Sage et al, 1986), and subsequently described as a c-Jun-responsive target gene that can be repressed or induced depending on cell type (Mettouchi et al, 1994;Briggs et al, 2002). Consistent with a role of SPARC in cellular stress, recent studies showed that SPARC protects lens epithelial cells from stress-induced apoptosis and suppresses apoptosis in pulmonary fibroblasts (Weaver et al, 2008;Chang et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…The intracellular signaling pathways downstream from SPARC are beginning to be identified. They include major mediators of integrin signaling such as integrin-linked kinase (ILK) and focal adhesion kinase (FAK) (Barker et al, 2005;Shi et al, 2007;Weaver et al, 2008), as well as b-catenin and phosphatidylinositol 3-kinase (PI3K)-Akt signaling pathways (Shi et al, 2004;Nie and Sage, 2009;Chang et al, 2010). In cancer, SPARC may function as either a tumor suppressor or a pro-invasive factor depending on the tumor type and local extracellular milieu.…”
Section: Introductionmentioning
confidence: 99%